Impacto financiero de las compañías de transporte comercial de taxis en tiempos de pandemia COVID - 19, en la ciudad de Loja, periodo 2019 - 2022 - Ramón Rodríguez, Jenny del Cisne (2023)
Transportation is a fundamental pillar for the development and progress of each country, however, the presence of the Covid-19 pandemic generated a global crisis that profoundly affected the social and economic spheres. In Ecuador, several economic sectors were affected by the emergence of the health crisis, one of the main ones being transportation, due to the mobility restrictions imposed by the government to curb the spread of the virus, which prevented the free circulation of vehicles and thus led to a significant decrease in the demand for transportation services, especially cabs. Therefore, the present study proposed to analyze the financial situation of commercial cab transportation companies in the city of Loja during the period 2019-2022, highlighting the economic impact derived from the measures adopted to combat the pandemic. A mixed research approach was adopted, combining qualitative and quantitative elements, with exploratory and descriptive research. The financial statements of the 14 legally constituted companies, obtained from the Superintendence of Companies, Securities and Insurance, were thoroughly examined. In addition, structured interviews were conducted with six General Managers of the cab companies using the non-probabilistic consecutive sampling technique. For the financial analysis, the technique of vertical and horizontal analysis was used; the application of key financial indicators, such as liquidity, indebtedness and profitability (ROA and ROE), to examine the impact of the accounting accounts of Assets, Liabilities, Equity, Income, Costs and Expenses, this made it possible to understand the distribution of resources, as well as to compare and identify variations over the years under study. The results highlighted a decrease in liquidity for the year 2020, with low levels of debt to assets and equity. This resulted in a reduction in ROA and ROE yields of 3.26% and 5.56%, respectively. Based on these findings, specific strategies were proposed to improve the economics of the sector, such as implementing measures to strengthen the financial health of the companies, exploring possibilities in expanding services and adapting to changing market conditions. In conclusion, the pandemic had a significant financial impact on cab companies in the city of Loja, evidenced by the decrease in liquidity and performance. Therefore, it is important to implement strategic actions in order to improve the economic situation of the sector in the future.